ADAPTIVE TIME-STEPPING FOR INCOMPRESSIBLE FLOW PART II: NAVIER-STOKES EQUATIONS - Kay, D; Gresho, P; Griffiths, D; Silvester, D (2010)
We outline a new class of robust and efficient methods for solving the Navier- Stokes equations. We describe a general solution strategy that has two basic building blocks: an implicit time integrator using a stabilized trapezoid rule with an explicit Adams-Bashforth method for error control, and a robust Krylov subspace solver for the spatially discretized system. We present numerical experiments illustrating the potential of our approach. © 2010 Society for Industrial and Applied Mathematics.